eportfolios for affordable learning solutions programs [electronic resource] (MERLOT, 2020)
Quoted from the homepage: Open Educational Practices and Affordable Learning: MERLOT and SkillsCommons has been instrumental in a number of Affordable Learning programs that reduce the costs of course materials for students by providing access to over 7,000 free and open etextbooks and simultaneously searching over 70 additional open libraries. Sharing open educational practices of how faculty migrated from print textbooks and how they teach with OER is a critical strategy for changing faculty and campus culture to implement Affordable Learning Solutions programs. Capturing OEP in ePortfolios: MERLOT customized ePortfolio templates within its Content Builder application for faculty to share their adoption of free and open educational resources with the support of scaffolding questions about: The OER adopted for their courses. The courses they are teaching, including sharing their course syllabus and sample learning assignments. Most courses are general education courses common across higher education. The reasons why they changed to OER and low cost course materials; sometimes surveys of students' reactions to the OER are included. Explore over 100 open teaching ePortfolios by faculty (mostly California and MERLOT partners) adopting OER